Геотектонічна періодизація раннього докембрію - Кирилюк, В.П. (Геологічний журнал, 2010)
Обоснована целесообразность использовании применительно к раннему докембрию геотектонической периодизации наряду с традиционной хроностратиграфической периодизацией, Предлагается схема геотектонической периодизации, которая включает два этапа раннедокембрийской структурно-вещественной эволюции фундамента щитов, или мегахрона — эогей и протогей, каждый из которых подразделяется на раннюю и позднюю стадии, или геохроны. The article provides the reasoning behind the usefulness of applying the method of geotectonic periodization, as well as the traditional chronosratigraphic periodization, to the early Precambrian. It proposes a model ol geotectonic periodization that includes two stages of early Precambrian structure-material evolution of the shield's foundation (or megachronos) — Eogeos and Protogeos — each of which can be further subdivided into early and late stages, or geochrons.